Developing smart tire pressure monitoring system: A performance evaluation of ESP32-C3 with ESP-NOW communication - Muhammad, Reftito Indi; Mutiara, Giva Andriana; Alfarisi, Muhammad Rizqy; Meisaroh, Lisda; Saleh, Abdul Rahman (Review of Computer Engineering Research, 2025)
This study aims to develop a low-cost and energy-efficient Tire Pressure Monitoring System (TPMS) that provides real-time monitoring of tire pressure and temperature using IoT-based wireless communication. The system was built using the MS5803-14BA sensor, ESP32-C3 microcontroller, and ESP-NOW wireless protocol. Performance was tested through laboratory and real-world scenarios and compared to two commercial TPMS systems (Level A and B). The proposed TPMS achieved 95.91% accuracy, closely aligning with Level A (99.87%) and slightly outperforming Level B (95.35%). It showed the highest temperature sensitivity (10.00%) while maintaining stable pressure readings (6.45%). In contrast, Level B exhibited greater pressure fluctuation (9.68%). The ESP-NOW protocol enabled reliable, low-power data transmission without interference. The developed system delivers high accuracy in detecting tire conditions in real time and demonstrates superior power efficiency and environmental stability, making it a strong alternative to traditional RF-based TPMS solutions. This system can be integrated into smart vehicles or fleet management platforms, enhancing safety through real-time alerts and enabling predictive maintenance. Future enhancements will include broader IoT connectivity, improved calibration, and extended testing in extreme conditions.